Implementasi Edukasi Digital SEHATI dan Pangan Lokal dalam Pencegahan Anemia pada Ibu Hamil - Fatimah, Siti; Rohmah, Siti; Purnamasari, Kurniati Devi; Sari, Deassy Ratna Juwita; Kurniasih, Ira (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: The prevalence of anemia among pregnant women in Sukamulya Village has reached 60%, which is considerably higher than the provincial and national rates, indicating the need for educational and sustainable interventions. This community service program aimed to improve knowledge and preventive behaviors related to anemia through culturally based nutrition education and local food empowerment utilizing the SEHATI Digital Education innovation. Methods: This study employed a community service (PkM) program approach with a pre–post test design involving 60 participants (30 pregnant women and 30 posyandu cadres). The intervention included cadre training, education sessions for pregnant women, interactive modules, Sundanese-language educational videos, and a mobile-based digital application. Results: The implementation of Digital SEHATI increased pregnant women’s knowledge scores regarding anemia, iron (Fe) tablet consumption, and the utilization of local foods, from a mean pre-test score of 58 to 79 on the post-test (±36% increase). These findings indicate that the SEHATI digital education media has the potential to enhance health education outcomes compared to conventional approaches and support the establishment of the “Ibu Hamil Sadar Gizi Sukamulya (ISGS)” group as a platform for program sustainability. Conclusion: Technology-based nutrition education, combined with local food empowerment, effectively improved knowledge, health behaviors, and community capacity to prevent anemia among pregnant women.